You have the following system of equations:
5x + y = 7 (1)
20x + 2y = 7 (2)
In order to solve the previous system, you proceed as follow:
multiply by 2 the first equation:
(5x + y = 7)(2)
10x + 2y = 14
next, you subtract the second equation of the system to the previoues equation:
10x + 2y = 14
-20x - 2y = - 7
-10x + 0 = 7
next, solve for x in the previous equation:
-10x = 7
x = -7/10
next, replace the previous obtained value of x into the first equation, and solve for y:
5x + y = 7
5(-7/10) + y = 7
-35/10 + y = 7
y = 7 + 35/10
y = (70 + 35)/10
y = 105/10 = 21/2
Hence, the solution to the given equation is:
x = -7/10
y = 21/2